Extremely low-frequency electromagnetic fields facilitate both osteoblast and osteoclast activity through Wnt/β-catenin signaling in the zebrafish scale - Kobayashi-Sun, Jingjing; Kobayashi, Isao; Kashima, Makoto; Hirayama, Jun; Kakikawa, Makiko; Yamada, Sotoshi; Suzuki, Nobuo (Frontiers in Cell and Developmental Biology, 2024)
Electromagnetic fields (EMFs) have received widespread attention as effective, noninvasive, and safe therapies across a range of clinical applications for bone disorders. However, due to the various frequencies of devices, their effects on tissues/cells are vary, which has been a bottleneck in understanding the effects of EMFs on bone tissue. Here, we developed an in vivo model system using zebrafish scales to investigate the effects of extremely low-frequency EMFs (ELF-EMFs) on fracture healing. Exposure to 10 millitesla (mT) of ELF-EMFs at 60 Hz increased the number of both osteoblasts and osteoclasts in the fractured scale, whereas 3 or 30 mT did not. Gene expression analysis revealed that exposure to 10 mT ELF-EMFs upregulated wnt10b and Wnt target genes in the fractured scale. Moreover, β-catenin expression was enhanced by ELF-EMFs predominantly at the fracture site of the zebrafish scale. Inhibition of Wnt/β-catenin signaling by IWR-1-endo treatment reduced both osteoblasts and osteoclasts in the fractured scale exposed to ELF-EMFs. These results suggest that ELF-EMFs promote both osteoblast and osteoclast activity through activation of Wnt/β-catenin signaling in fracture healing. Our data provide in vivo evidence that ELF-EMFs generated with a widely used commercial AC power supply have a facilitative effect on fracture healing.